The dividend policy of companies listed on the Warsaw Stock Exchange - Bogołębska, Justyna (Polityka dywidendowa firm notowanych na warszawskiej Giełdzie Papierów Wartościowych, 2019)
Dividend policy is created and formulated by companies. For this reason, the focus of the analysis is on the message conveyed by the information on the dividend payout, the relationship between the dividend and financial indicators, the continuity of the payout and the amount of the dividend itself. Decisions on the dividend payment include two basic issues: what portion of profits should be paid out over a certain period of time and whether the company should maintain a steady and stable growth rate. If a steady and stable growth rate is maintained, then the level of earnings will increase from year to year. This phenomenon is confirmed by the growing number of companies paying dividends. The purpose of the article is to indicate significant differences in stock prices before the dividend payment and after the dividend payment, and to indicate significant differences in stock prices before the announcement of the dividend right and after the announcement of the dividend right
Financial Sciences. Nauki o Finansach, 2019, vol. 24, no. 2, s. 17-27
Keywords: dividend policy; sharpe price; investment decisions; polityka dywidendowa; cena akcji; decyzja inwestycyjna